2016
DOI: 10.17507/tpls.0602.24
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teaching Communicative Strategy on EFL Learners’ Willingness to Communicate

Abstract: Abstract-While attaining language proficiency has turned to a main concern of many, how to do so is still one of the biggest secrecy in TEFL field. With regards to improving learner's language proficiency, MacIntyre postulated willingness to communicate (WTC) as one of the best predictors of being a proficient learner. Moreover, perceiving the status quo of many competent learners who avoid communication as well as their narrow chance in getting proficiency, the researcher attempted to investigate whether teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
1
14
0
2
Order By: Relevance
“…The lack of significant improvement in the control group depicted that simply offering communicative practice to learners using the polytechnic module was not sufficient to ensure improvement in oral communication ability. The results were consistent with studies of Mirsane and Khabiri (2016), Nakatani (2010), Rabab'ah (2015 and Teng (2012). However in Nakatani's study, it did not include strategies for own performance problem such as approximation and circumlocution because Nakatani reasoned that these strategies are directly relying as an internal psycholinguistic mechanism in order to solve particular lexical problems and are not an overtly interactive in nature.…”
Section: Discussionsupporting
confidence: 79%
“…The lack of significant improvement in the control group depicted that simply offering communicative practice to learners using the polytechnic module was not sufficient to ensure improvement in oral communication ability. The results were consistent with studies of Mirsane and Khabiri (2016), Nakatani (2010), Rabab'ah (2015 and Teng (2012). However in Nakatani's study, it did not include strategies for own performance problem such as approximation and circumlocution because Nakatani reasoned that these strategies are directly relying as an internal psycholinguistic mechanism in order to solve particular lexical problems and are not an overtly interactive in nature.…”
Section: Discussionsupporting
confidence: 79%
“…After 16 sessions of strategy training in their study, they found out that the learners appeared to be more willing to use the strategies and to communicate. Mirsane and Khabiri (2016) explained these results referring to MacIntyre and Noels (1994) estimating that strategy training helps the learners cope with negative psychology and comforts them to communicate in L2. Mehrgan (2013), on the other hand, explored socio-affective strategy use of the learners who are already willing to communicate.…”
Section: The Relationship Between Language Learning Strategy Use and mentioning
confidence: 98%
“…In addition, Öz, Demirezen, and Pourfeiz (2015) suggested that high levels of WTC lead to improving L2 achievement besides providing an environment for successful communication. According to MacIntyre and Doucette (2010), second language learning can be enhanced by increased levels of WTC among the language learners, and therefore researchers need to focus on how to do that especially in EFL contexts (Mirsane & Khabiri, 2016).…”
Section: Willingness To Communicate In L2mentioning
confidence: 99%
See 2 more Smart Citations